EVALUATION OF ORTHOSTATIC POSTURE OF HELICOPTER PILOTS: IMPLICATIONS OF THE POSTURE ADOPTED IN COCKPIT AND OF A WORK JOURNEY (Fiep Bulletin - online, 2015)
Helicopter pilots is obligated to maintain an asymmetrical posture in the cockpit due to the position of the aircraft controls, remaining during all flight long, which may last several hours in the same position, seated with the trunk slightly bent forward and rotated to the left, keeping the four extremities of their body in the function of piloting the aircraft. Thus, their mobility is limited and their normal movements to decrease the discomfort of the immobility itself is not possible. This is one of the main etiological factors reported in the literature for the high incidence of low back pain in such workers. This study performed a postural evaluation of helicopter pilots in the orthostatic posture, aiming at identify the presence of postural deviation in such professionals, and if this has any relationship with the posture adopted during the flight. Moreover, any postural alteration after a work journey was evaluated. A computerized analysis system was employed for such assessment, which allows for quantitative and qualitative evaluation. The sample comprised 41 male helicopter pilots. A high incidence of some postural alteration was observed in the sample, being one of the most important the gibosity (58.5% on right and 14.6% on left hand side). Regarding the postural alterations after a work journey, only abduction and lateral rotation of the scapula presented statistical significance difference (p
Keywords: helicopter's pilot; body posture; low back pain.